02.09 Identification of a novel pro-inflammatory T cell epitope from his-trna-synthetase associated with interstitial lung disease in anti-jo-1 positive patients. (1st March 2017) - Galindo-Feria, Angeles Shunashy; Albrecht, Inka; Notarnicola, Antonella; Dastmalchi, Maryam; Dubnovitsky, Anatoly; Sandalova, Tatiana; Kozhukh, Genadiy; Rönnblom, Lars; Achour, Adnane; Malmström, Vivianne; Lundberg, Ingrid E
Abstract : Background: Previous studies have demonstrated that CD4 + T cells from peripheral blood of anti-histidyl-tRNA synthetase (anti-His-tRNA) also known as anti-Jo-1 positive patients proliferate in response to stimulation with full-length His-tRNA and a N-terminal fragment comprising residues 1–60. In this study we present a novel epitope that identifies patients with moderate-severe interstitial lung disease (ILD). Materials and Methods: Sixteen anti-Jo-1 positive patients with antisynthetase syndrome followed at the Karolinska University Hospital were enrolled. As controls we included HLA-DRB1*03-positive healthy individual (HCs, n=8). Peripheral blood mononuclear cells were isolated by Ficoll-Hypaque density centrifugation and in vitro stimulated with: a) full length His-tRNA protein; b) a novel HLA-DR*03:01 binding peptide from native His-tRNA; c) an altered peptide ligand (APL) variant of His-tRNA designed to prevent recognition by HLA-DR3/His-tRNA-specific TCRs. T cell activation was assessed by CD40L up-regulation and expression of pro-inflammatory cytokines (IFN-g, IL-2 and IL-17A) by flow cytometry. Clinical and laboratory data were documented and analysed by Student's T test or Mann-Withney U-test. Results: At the time of blood sampling the patients had a mean age of 58 years (48–83 years), median disease duration of 50 months (11–70 months), MMT8 score 80 (79-80), HAQ 0.25 (0 13-0.75). Eighty-four percent were female, 13/16 patients had ILD and 13/16 had muscle weakness. T cell activation towards the novel His-tRNA peptide was observed in 2/16 anti-Jo-1 positive patients. When stimulating with the APL, no T cell activation was observed in one of the patients that was reactive for the peptide. For evaluation of pro-inflammatory features, the His-tRNA-specific T cells displayed significant up-regulated levels of IFN-γ (p<0.05) compared to HC (p<0.05). Additionally, 1/8 HCs displayed a modest response to both the novel His-tRNA peptide and the full length His-tRNA protein. In this context only IL-2 was observed. The patients that showed an upregulation of CD40L had a moderate-severe clinical progression of ILD. Conclusion: In this study, we demonstrate the presence of His-tRNA-reactive CD4 + T cells in peripheral blood from anti-Jo-1 positive patients and a novel His-tRNA peptide, characterised by the expression of IFN-g. This phenotype seemed to correlate to a moderate-severe clinical progression of ILD.